Child and Adolescent Integration to International Labour: The Case of Costa Rica Based on Supplied Data by the X Census of Population and VI of Housing, 2011. (Revista Rupturas, 2016)
The article problematizes about the incorporation of Children and Adolescent immigrants in the international workforce, mainly thinking about the needs of this population to obtain better life conditions amid a context based on unequal development that inhibits the States in the fulfillment of the rights of this population. To accomplish this, was made a search about the state of satisfaction of basic needs of this population in Costa Rica, using to the data recorded by X Census of Population and VI of Housing , 2011, at the REDATAM system. It ends with a reflection about Social Moratorium category and the limitations that this perspective has in a context of unequal development so that children and young migrant workers may be able to build autonomous and emancipated life projects
Keywords: Migrant children; migrant youth; international migration; unsatisfied basic needs; child and adolescent labor